2019
DOI: 10.1016/j.colsurfb.2018.12.048
|View full text |Cite
|
Sign up to set email alerts
|

Diethyldithiocarbamate loaded in beeswax-copaiba oil nanoparticles obtained by solventless double emulsion technique promote promastigote death in vitro

Abstract: Leishmaniasis is considered a neglected tropical disease that represents a Public Health problem due to its high incidence. In the search of new alternatives for Leishmaniasis treatment diethyldithiocarbamate (DETC) has shown an excellent leishmanicidal activity and the incorporation into drug carrier systems, such as solid lipid nanoparticles (SLNs), is very promising. In the present work DETC loaded in beeswax nanoparticles containing copaiba oil were obtained by the double emulsion/melt technique. The nanop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 48 publications
4
12
0
Order By: Relevance
“…Particularly, it has been widely used to incorporate insulin into the matrices of SLNs and NLCs for oral delivery [ 102 , 103 , 104 ]. According to this method, a drug and a stabilizer are dissolved in an aqueous solution and then emulsified in a water-immiscible organic phase containing lipids [ 105 ] or in solvent-free molten lipids [ 106 , 107 ]. These primary emulsions are dispersed in an aqueous phase containing a hydrophilic emulsifier to form water/oil/water (w/o/w) emulsion.…”
Section: Methods For Slns and Nlcs Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…Particularly, it has been widely used to incorporate insulin into the matrices of SLNs and NLCs for oral delivery [ 102 , 103 , 104 ]. According to this method, a drug and a stabilizer are dissolved in an aqueous solution and then emulsified in a water-immiscible organic phase containing lipids [ 105 ] or in solvent-free molten lipids [ 106 , 107 ]. These primary emulsions are dispersed in an aqueous phase containing a hydrophilic emulsifier to form water/oil/water (w/o/w) emulsion.…”
Section: Methods For Slns and Nlcs Preparationmentioning
confidence: 99%
“…After w/o/w emulsion was formed, the emulsion was poured into cold water (2–5 °C) to solidify NLCs [ 107 ]. A similar strategy was used to prepare diethyldithiocarbamate-loaded SLNs with PSs of <200 nm and EEs of >80% [ 106 ]. The advantage of the double emulsion method is that it does not require molten lipid.…”
Section: Methods For Slns and Nlcs Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…The double emulsion can fix the problem of low encapsulation efficiency of hydrophilic drugs in o/w emulsion since hydrophilic molecules are often encapsulated using w/o/w emulsion method. Several studies have reported the interest of using a double emulsionevaporation process in drug delivery [9], [21]. Recently, w/o/w emulsion was produced to encapsulate Memantine, an approved anti-Alzheimer agent, into PLGA nanoparticles.…”
Section: Figure 3 Formation Of O/w Emulsion By Single Emulsion Evaporationmentioning
confidence: 99%
“…It demonstrated potent in vitro efficacy, and it almost completely suppressed parasite replication in the spleen, whereas it also inhibited the parasite replication in the liver. Mazur et al (2019) devised beeswax nanoparticles containing copaiba oil to encapsulate diethyldithiocarbamate, which has previously shown excellent leishmanicidal effect. The nanoformulation decreased the cytotoxic effects of the drug against macrophages, which led to an almost 2-fold increase in the selectivity index.…”
Section: Lipid Nanosystems Encapsulating Approved Drugsmentioning
confidence: 99%